Unveiling Heritage Through Space: A Spatial Analysis of Tourist Behavior in Kampung Kayutangan, Malang - Putu Ratih Deandra Putri; Jenny Ernawati; Herry Santosa (University of Merdeka Malang, 2026)
Malang City is renowned for its rich local wisdom and well-preserved colonial-era heritage in East Java. Kampung Kayutangan is a settlement that exemplifies the cultural depth of the city and serves as a significant destination for heritage tourism. This study examines how spatial structures and local knowledge affect tourist experiences by incorporating space syntax analysis with axial and visibility graph analysis to forecast pedestrian movement by evaluating spatial connectivity and visibility, utilizing place-centered mapping results derived from field observations. The findings demonstrate that while syntactic indicators reveal spatial hierarchies and accessibility, visitors are often drawn to culturally meaningful locations, even if these sites possess lower visibility. The study underscores the importance of incorporating local knowledge and historical context into urban spatial planning. By linking analytical methods with grounded cultural insights, this research presents a framework for sustainable heritage management and design that honors the identity and memory of a place. Planning strategies should accommodate cultural assets by enhancing accessibility, signage, and amenities to culturally significant yet spatially disconnected areas and ensuring that local wisdom continues to inform and enrich contemporary urban development.